Emergent evolution of first-order phase transitions from magneto-structural to magneto-elastic in MnCo1−y Fe y Ge1−x Si x alloys - Yong Li; Xinyue Ye; Lingwei Li; Enke Liu (JPhys Energy, 2023)
The emergent evolution of first-order phase transitions from magneto-structural to magneto-elastic and magnetocaloric effect (MCE) have been investigated by X-ray diffraction, differential scanning calorimetry and magnetization measurements. Applying the isostructural alloying principle, the martensitic transition temperature ( T _M ) increases effectively and the Curie temperatures of the two phases increase slightly by substituting the Si content ( x ). With an appropriate amount of Fe and Si content, an emergent first-order antiferromagnetic–ferromagnetic magnetoelastic transition with thermal hysteresis in the martensitic state occurs for MnCo _0.7 Fe _0.3 Ge _1– _x Si _x ( x = 0.15–0.40) alloys, which results from the decrease in the nearest-neighbor Mn–Mn distance. Moreover, the values of magnetic entropy change (Δ S _M ), refrigeration capacity (RC) and temperature-averaged entropy change (TEC, 10 K) with Δ H = 50 kOe reach −12.2 J kg ^−1 K ^−1 , 112.8 J kg ^−1 and 11.4 J kg ^−1 K ^−1 for MnCo _0.7 Fe _0.3 Ge _0.8 Si _0.2 undergoing the ferromagnetic magneto-structural transition in the Curie temperature window. The results facilitate the magnetocaloric/magnetoelastic performance and tunability of multiple phase states in a wider temperature range.